The Role of Storytelling in Developing Children's Emotional Intelligence - Sabrina, Rifdah; Fadli Rambe, Khairul; Rahmi, Azvi; Zeky, Serpuadi (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2025)
This research is based on the author's observations at Ammatullah Kuranji Islamic Kindergarten, Padang, in April 2025. It was found that children's emotional intelligence was still not well managed, because there were still many students who lacked focus, disturbed their friends, and other actions in the teaching and learning process. Children's emotional intelligence needs to be managed, therefore learning must be interesting and fun. One way to manage children's emotional intelligence is through the storytelling method. This study aims to (1) Identify factors that influence children's emotional intelligence at Ammatullah Kuranji Islamic Kindergarten, Padang, 2024-2025 academic year; and (2) Develop strategies for managing children's emotional intelligence through the storytelling method at Ammatullah Kuranji Islamic Kindergarten, Padang, 2024-2025 academic year. This study uses a quantitative research method, the subjects in this study were students at Ammatullah Kuranji Islamic Kindergarten, Padang. The number of students who became subjects was 30 children. This research was collaborative between class teachers, the principal, and the author. The results of this study indicate that there was an increase in children's emotional intelligence management through storytelling, with a 34% increase in pre-test emotional intelligence and an 86.7% increase in post-test emotional intelligence. The conclusion of this study is that children's emotional intelligence can be managed through storytelling.